If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4x + -4 = 11x + -81 Reorder the terms: -4 + 4x = 11x + -81 Reorder the terms: -4 + 4x = -81 + 11x Solving -4 + 4x = -81 + 11x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-11x' to each side of the equation. -4 + 4x + -11x = -81 + 11x + -11x Combine like terms: 4x + -11x = -7x -4 + -7x = -81 + 11x + -11x Combine like terms: 11x + -11x = 0 -4 + -7x = -81 + 0 -4 + -7x = -81 Add '4' to each side of the equation. -4 + 4 + -7x = -81 + 4 Combine like terms: -4 + 4 = 0 0 + -7x = -81 + 4 -7x = -81 + 4 Combine like terms: -81 + 4 = -77 -7x = -77 Divide each side by '-7'. x = 11 Simplifying x = 11
| x-2=2x-men | | 60-3x=6x+21 | | 7x+14=10x+5 | | 2x-10=-2+18 | | 5x+8=53 | | 5x+40=60 | | (x+3)=x+10 | | 2n+9=-29 | | 2x+20=8x+2 | | 10x^2-3c-27= | | 5x+18=13x-62 | | 16x^2-41x+25=0 | | 2x=9x-28 | | 12+b/6=16 | | 5a+6=41 | | -6k^2-13k-6= | | 2(4x+2)=28 | | 2x-16=3(2x+2)-2 | | -3x+20=8 | | 64-5x=3x+14 | | -2x+15=3x-40 | | 6x=8x-4 | | 3+4n=15 | | 3x=36-6x | | -2h^2+5h+3= | | -8x+4=2 | | 5y-7=-3 | | (8+5)n=53 | | 105-7x=11x+23 | | 2x-men=4x+3 | | (5+8)n=53 | | 5x-2=3x-8 |